2014
DOI: 10.3920/bm2013.0061
|View full text |Cite
|
Sign up to set email alerts
|

Heat-killed probiotic bacteria differentially regulate colonic epithelial cell production of human β-defensin-2: dependence on inflammatory cytokines

Abstract: The inducible antimicrobial peptide human β-defensin-2 (hBD-2) stimulated by pro-inflammatory cytokines and bacterial products is essential to antipathogen responses of gut epithelial cells. Commensal and probiotic bacteria can augment such mucosal defences. Probiotic use in the treatment of inflammatory bowel disease, however, may have adverse effects, boosting inflammatory responses. The aim of this investigation was to determine the effect of selected probiotic strains on hBD-2 production by epithelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 39 publications
0
33
0
3
Order By: Relevance
“…Lactic acid bacteria have been used in many fermented foods around the world and are well adapted to human life. Several strains of lactic acid bacteria have been reported to induce the expression of antimicrobial peptides . In addition, we have revealed that the upregulation of β‐defensin by L. helveticus is higher than other Lactobacillus species in vitro (unpublished data).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Lactic acid bacteria have been used in many fermented foods around the world and are well adapted to human life. Several strains of lactic acid bacteria have been reported to induce the expression of antimicrobial peptides . In addition, we have revealed that the upregulation of β‐defensin by L. helveticus is higher than other Lactobacillus species in vitro (unpublished data).…”
Section: Introductionmentioning
confidence: 72%
“…Several strains of lactic acid bacteria have been reported to induce the expression of antimicrobial peptides. [13][14][15] In addition, we have revealed that the upregulation of β-defensin by L. helveticus is higher than other Lactobacillus species in vitro (unpublished data). For these reasons, dietary intake of LH2171 is considered suitable for upregulating the expression of β-defensins.…”
mentioning
confidence: 80%
“…Accordingly, an increase in the antimicrobial activity of the intestinal fluids that lead to a breakdown of the bacteria was observed by using electronic microscopy. Habil et al [37] concluded that probiotic strains differentially regulate human beta 2 defensin mRNA expression and protein secretion. These modulations were guided by inflammatory stimulus and cytokine environment.…”
Section: Mechanisms Induced By Probiotics To Stimulate the Immune Systemmentioning
confidence: 99%
“…Gut microbes have been shown to differentially regulate defensin expression and protein secretion, which is influenced by local inflammatory mediators. 36 Metabolites from the microbiome induce epithelial cell inflammasome signaling, resulting in IL-18 secretion and antimicrobial peptide production. 37 Interestingly, host genetic deficiency in this pathway results in dysbiosis, and this dysbiotic microbiome can hijack the microbiome of wildtype animals.…”
Section: Innate Immune Systemmentioning
confidence: 99%